2017
DOI: 10.1002/wmh3.226
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Inequalities in Health and Access to Health Services: Evidence From New York City

Abstract: In Manhattan, the rate of hospital discharges for avoidable hospital conditions (AHC), a measure of access to timely and effective ambulatory care, fell by nearly 50 percent between 1999 and 2013. Despite this remarkable improvement, there has been virtually no change in racial, ethnic, or neighborhood‐level differences in rates of AHC. This is surprising given New York City's emphasis on public health and its efforts to reduce health and health‐care inequalities. We discuss the policy implications of these fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…The study corroborates with the literature reporting "racial, ethnic, and neighborhood-level inequalities in health and healthcare are a long-standing problem in the United States" (Gusmano et al 2017;187). Furthermore, persistent inequalities of neighborhoods, including income inequality, racial segregation, and concentrated poverty, remain barriers to reducing and eliminating disparities in access to healthcare and, ultimately, achieving health equity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study corroborates with the literature reporting "racial, ethnic, and neighborhood-level inequalities in health and healthcare are a long-standing problem in the United States" (Gusmano et al 2017;187). Furthermore, persistent inequalities of neighborhoods, including income inequality, racial segregation, and concentrated poverty, remain barriers to reducing and eliminating disparities in access to healthcare and, ultimately, achieving health equity.…”
Section: Discussionsupporting
confidence: 89%
“…A plethora of literature suggests an association between race, ethnicity, and health as a primary function of socioeconomic status (income and education) (Lawrence, 2002). At the neighborhood-level, race-based residential discrimination and segregation among blacks and Hispanics, along with high concentrations of poverty "sustain racial patterns of healthcare delivery," where blacks and Hispanics more likely to be uninsured and face financial disadvantages with medical debt (Gusmano et al 2017;188). As a limitation the study is primarily descriptive due to its small sample.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of access to primary care in NYC found that gender, insurance status, racial, ethnic, and neighborhood-level disparities did not change over the course of the Bloomberg administration. 14 Our findings on revascularization are similar. Although there were notable reductions in racial and ethnic disparities in the use of revascularization procedures, gender, insurance status, and neighborhood-level differences were conspicuously stable over the time periods we examined.…”
Section: Introductionsupporting
confidence: 72%
“…Yet another hypothesis is that reductions in the ACSC rate depend not only on extending insurance but on addressing underlying social factors that lead to poor health, poor health behaviours and different health-seeking behaviours. Although we found that the ACSC rate in New York fell by about half, between 2000 and 2013, the differences by insurance status, race, ethnicity and neighbourhood have not changed over this period (Gusmano et al ., 2017). As Bradley et al .…”
Section: Discussionmentioning
confidence: 99%